Impact of prenatal amoxicillin exposure on hippocampal development deficiency. (1st February 2023) - Qin, Jiaxin; Yao, Baozhen; Xie, Lulu; Wang, Tingting; Zhang, Shuai; Luo, Mingcui; Wang, Hui; Xu, Dan; Peng, Biwen
Abstract: Background: Amoxicillin has been widely used to treat infectious diseases during pregnancy. Current studies suggest that amoxicillin exposure during pregnancy could lead to developmental disorders in the offspring and increase the incidence of long-term complications such as asthma and kidney damage in adulthood. However, the adverse effects of prenatal amoxicillin exposure (PAmE) including administration stage, doses and courses on fetal hippocampal neurodevelopment and its function in the offspring have not been elucidated. In this study, we intend to investigate the effects of PAmE on fetal hippocampal development and its possible mechanisms. Method: Pregnant Kunming mice were given intragastric administration with amoxicillin at different administration stage, doses and courses, and GD (gestational day) 18 offspring hippocampus was collected for morphological and development-related functional assays, and the molecular mechanisms were explored. Results: PAmE induced hippocampal hypoplasia in the offspring with suppressed hippocampal neuronal cell proliferation and impaired neuronal synaptic plasticity comparatively; hippocampal astrocyte and microglia were damaged to varying degrees. The developmental toxicity of PAmE in fetal mices varies by time, dose, and course of treatment. The most severe damage was observed in the late gestation, high dose, and multi-course dosing groups. The significant reduction either in SOX2, an essential gene in regulating neural progenitor cell proliferation, and reduction of genes related to the Wnt/β-catenin pathway may suggest that the key role of SOX2/Wnt/β-catenin pathway in impaired hippocampal development in the offspring due to PAmE. Conclusion: In this study, PAmE was found to be developmentally toxic to the hippocampus thus to induce developmental damage to various hippocampal cells; Even with current clinically safe doses, potential hippocampal damage to offspring may still present; This study provides a theoretical and experimental basis for guiding the rational usage of drugs during pregnancy and giving effectively assessment of the risk on fetal hippocampal developmental toxicity. Graphical abstract: Image 1 Highlights: PAmE leads to reduced proliferation and impaired synaptic development of progeny hippocampal neuronal cells. The most devastating toxic window effects occur in late pregnancy, during high-dose and multiple-course administration. SOX2/Wnt/β-catenin signaling may be involved in PAmE-induced developmental toxicity in the fetal hippocampus.